Liquid-liquid equilibrium data and thermophysical properties for ternary systems composed of water, acetic acid and different solvents - Hadlich de Oliveira, Leonardo (2019)
Liquid-liquid equilibrium (LLE) data for water + acetic acid + {1-butanol or isopentanol or methyl-terc-butyl ether (MTBE) or methyl isobutyl ketone (MIBK) or diisobutyl ketone (DIBK) or isoamyl propionate} systems at T = {293.2 and 313.2} K and P ≈ 95 kPa were determined. Immiscibility region (LLE envelope) were determined experimentally through binodal curves (cloud point data). Thermophysical properties, i.e., density, refractive index, speed of sound, isentropic compressibility and molar refractivity were obtained for each cloud point. Tie lines were attained using indirect method utilizing equations obtained through cloud point data fit and partition coefficients, selectivities and percent of extraction were calculated in order to evaluate the effects of solvent type and temperature on acetic acid removal from water. Besides, thermophysical properties for all systems were compared. LLE data were correlated with NRTL model, presenting root mean square deviation equal to 1.2366% for 66 tie lines. NRTL modelling also estimated plait points for all systems.